Nitrogen, Oxygen‐Codoped Vertical Graphene Arrays Coated 3D Flexible Carbon Nanofibers with High Silicon Content as an Ultrastable Anode for Superior Lithium Storage. Issue 6 (6th January 2022) - Mu, Yongbiao; Han, Meisheng; Wu, Buke; Wang, Yameng; Li, Zhenwei; Li, Jiaxing; Li, Zheng; Wang, Shuai; Wan, Jiayu; Zeng, Lin
Abstract: Free‐standing and foldable electrodes with high energy density and long lifespan have recently elicited attention on the development of lithium‐ion batteries (LIBs) for flexible electronic devices. However, both low energy density and slow kinetics in cycling impede their practical applications. In this work, a free‐standing and binder‐free N, O‐codoped 3D vertical graphene carbon nanofibers electrode with ultra‐high silicon content (VGAs@Si@CNFs) is developed via electrospinning, subsequent thermal treatment, and chemical vapor deposition processes. The as‐prepared VGAs@Si@CNFs electrode exhibits excellent conductivity and flexibility because of the high graphitized carbon nanofiber network and abundant vertical graphene arrays. Such 3D all‐carbon architecture can be fabulous for providing a conductive and mechanically robust network, further improving the kinetics and restraining the volume expansion of Si NPs, especially with an ultra‐high Si content (>90 wt%). As a result, the VGAs@Si@CNFs composite demonstrates a superior specific capacity (3619.5 mAh g −1 at 0.05 A g −1 ), ultralong lifespan, and outstanding rate capability (1093.1 mAh g −1 after 1500 cycles at 8 A g −1 ) as a free‐standing anode for LIBs. It is believed that this work offers an exciting method for developing free‐standing and high‐energy‐density electrodes for other energy storage devices. Abstract : A free‐standing ultra‐high silicon content flexible anode with enhanced hydrophilicity is successfully developed by growing vertical graphene arrays on Si@CNFs (VGAs@Si@CNFs), which is regarded as "building blocks" and "bridges" to improve the conductivity the electrode, prevent the aggregation and pulverization of Si. This work casts new light on the high‐energy anode design for possessing rate capability and cycling stability.